Increased anxiety-like behaviors, but blunted cortisol stress response after neonatal hippocampal lesions in monkeys. (February 2017) - Raper, Jessica; Wilson, Mark; Sanchez, Mar; Payne, Christa; Bachevalier, Jocelyne
Highlights: Early hippocampal lesions cause increased anxiety-like and self-directed behaviors. Despite increased anxiety-like behaviors, monkey had a blunted cortisol stress response. Data is similar to adult-onset hippocampal damage in humans and monkeys. Implication for mood and psychiatric disorders with altered hippocampal development. Abstract: The hippocampus is most notably known for its role in cognition and spatial memory; however it also plays an essential role in emotional behaviors and neuroendocrine responses. The current study investigated the long-term effects of neonatal hippocampal lesions (Neo-Hibo) on emotional and hypothalamic-pituitary-adrenal (HPA) axis functioning. During infancy, unlike controls, Neo-Hibo monkeys exhibited enhanced expression of emotional behaviors (e.g. freezing, anxiety-like, and self-directed behaviors) when exposed to a human intruder (HI task). Upon reaching adulthood, they exhibited reduced freezing and hostility, but increased anxiety-like and self-directed behaviors during the HI task. Neo-Hibo monkeys behaved as if they systematically over-rated the risk inherent in the HI task, which supports Gray and McNaughton's septo-hippocampal theory of anxiety. Also, in adulthood, the increased levels of anxiety-like behaviors in Neo-Hibo monkeys were associated with a blunted cortisol response to the HI task. Examination of basal HPA axis function revealed that Neo-Hibo monkeys exhibited the typical diurnal cortisol decline throughout the day, but had lower cortisol concentrations in the morning as compared to controls. Taken together these data suggest that an intact hippocampus during development plays a larger role beyond that of inhibitory/negative feedback regulation of the HPA axis stress-activation, and may be critical for HPA axis basal functioning as well as for the stress response. The behavioral and neuroendocrine changes demonstrated in the current study are reminiscent of those seen in human or nonhuman primates with adult-onset hippocampal damage, demonstrating little functional compensation following early hippocampal damage.